The caregiving role following percutaneous coronary intervention - Rolley, John; Smith, J.; Digiacomo, Michelle; Salamonson, Y.; Davidson, Patricia (Blackwell Publishing, 2011)
Aim. The aim of this study is to describe the experience of caregivers of individuals who have had a percutaneous coronary intervention (PCI). Background. Decreased lengths of hospital stay and an increased emphasis on chronic disease self-management increase the importance of carers in assisting in recovery and lifestyle modification. Design. Cross-sectional dual-moderated focus group design. Method. Three focus groups using a dual facilitation approach were held in the cardiac rehabilitation setting of a tertiary referral hospital in metropolitan Sydney. All sessions were audio recorded, transcribed and thematically analysed. Results. Four themes emerged from the data: (1) a gendered approach to health, illness and caring; (2) shock, disbelief and the process of adjustment following PCI; (3) challenges and changes of the carer-patient relationship and (4) the needs of the carer for support and information. Issues emerging from this study parallel other findings describing the experience, yet provide new insights into the issues surrounding PCI.Conclusion. These findings highlight the need for including carers in care planning and decision-making and providing them with support and resources. Relevance to clinical practice. Emphasises the importance of preparing carers of the likely experience following a PCI. Demonstrates the degree to which vigilance, deferment of carer-health needs and role conflict impact on the carer's personal relationship. Demonstrates the need for formal support interventions for carers of patients who have had PCI.